EPISTEMOLOGI TAFSIR MIN HUDĀ AL-QUR`ĀN KARYA MUḤAMMAD TAQĪ AL-MUDARRISĪ - Aufa Varrassyah Nawwaf (AL ITQAN: Jurnal Studi Al-Qur'an, 2023)
Min Hudā Al-Qurān is an interpretation that has its own color and orientation within the discourse of Shia exegesis since it’s not trapped in the ideological vortex like most Shia interpretations. Its author, Muḥammad Taqī al-Mudarrisī, aims to create an interpretation that responds to social issues by reflecting on empirical realities. This research is necessary to reveal the essence, trace the sources and methods, and test the validity of the interpretation. This is a qualitative library research. The results of this research are as follows: First, al-Mudarrisī believes that interpretation must carry a pragmatic spirit and be able to provide solutions to community issues. Second, al-Mudarrisī’s interpretation is majority based on empirical realities and rational logics. The Qur'an, reality, and reason are dialogued using a functional paradigm. Third, the method used is al-manhaj al-taḥlīlī min khilāli al-rabṭ al-mawḍū’ī. Al-Mudarrisī systematically and sequentially analyzes the verses that have previously been grouped into a unified theme. Al-Mudarrisī also adopts al-manhaj al-tadabbur al-mubāshar, or direct contemplation of the Qur'anic verses. Fourth, Min Hudā Al-Qurān cannot be considered one hundred percent valid, whether in terms of coherence, correspondence, or pragmatism.